2019
DOI: 10.1021/acs.jmedchem.9b01201
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Small Molecule Dual Inhibitors Targeting Toll-Like Receptors 7 and 8

Abstract: Endosomal toll-like receptors (TLRs) 7 and 8 recognize viral single-stranded RNAs, a class of imidazoquinoline compounds, 8-oxo-adenosines, 8-aminobenzodiazepines, pyrimidines, and guanosine analogues. Substantial evidence is present linking chronic inflammation mediated specifically by TLR7 to the progression of autoimmunity. We identified a new TLR7/8 dual inhibitor (1) and a TLR8-specific inhibitor (2) based on our previous screen targeting TLR8. Compound 1, bearing a benzanilide scaffold, was found to inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…5, Table 1; . Furthermore, several compounds consisting of two distinct chemical scaffolds equipped with TLR7/8 dual or TLR8-selective antagonistic activities have recently been discovered (Padilla-Salinas et al, 2019).…”
Section: Inactivated Forms Of Tlr8 Stabilized By Antagonistsmentioning
confidence: 99%
“…5, Table 1; . Furthermore, several compounds consisting of two distinct chemical scaffolds equipped with TLR7/8 dual or TLR8-selective antagonistic activities have recently been discovered (Padilla-Salinas et al, 2019).…”
Section: Inactivated Forms Of Tlr8 Stabilized By Antagonistsmentioning
confidence: 99%
“…Yin’s lab identified a new TLR8 inhibitor bearing a 1,3,4-oxadiazole motif and a modest TLR7 and TLR8 dual inhibitor bearing a benzanilide scaffold. Both were selected for extensive SAR studies, and critical distinct scaffolds were established and optimized for each kind of inhibitor to enhance their specificity …”
Section: Tlr8mentioning
confidence: 99%
“…Both were selected for extensive SAR studies, and critical distinct scaffolds were established and optimized for each kind of inhibitor to enhance their specificity. 59…”
Section: ■ Tlr7mentioning
confidence: 99%
“…Benzanilide 145 (Figure ) was obtained from the HTS of a library of 14 400 compounds . The SAR study involving replacing one of the −CF 3 groups in 145 with a −H in ring A had revealed that one −CF 3 group was sufficient to hold the TLR7 and TLR8.…”
Section: Structural Evolution: Structure–activity Relationship Develo...mentioning
confidence: 99%
“…Benzanilide 145 (Figure 44) was obtained from the HTS of a library of 14 400 compounds. 131 The SAR study involving replacing one of the −CF 3 groups in 145 with a −H in ring A had revealed that one −CF 3 group was sufficient to hold the TLR7 and TLR8. Interestingly, switching the −CF 3 group to −F in 146 weakened the TLR7 activity with the retention of TLR8 activity.…”
Section: Structural Evolution and Structure−activity Relationship Of ...mentioning
confidence: 99%